Uwieczniać się jako gatunek ludzki - Jędraszewski, Marek (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2018)
In this article author analyses the value on being itself as a basis and reason for prolongation of the mankind. Against some nihilistic and existentialist philosophers and writers who denied the value of life-giving, author refers to thoughts of Emmanuel Levinas and Remi Brague and shows that, like in the ancient and scholastic philosophy, we can find here the belief that Being is essentially connected with the Good itself. Neitherscience (as well as ideologies it evolves), nor pessimistic overview can give us such a powerful perspective to mankind’s durability and its genuine value as a humanism,strengthened with religious faith, can do.